Diabetes. Issue 1 (January 2015) - Bomberg, Hagen; Kubulus, Christine; List, Franka; Albert, Noemi; Schmitt, Kathrin; Gräber, Stefan; Kessler, Paul; Steinfeldt, Thorsten; Standl, Thomas; Gottschalk, André; Wirtz, Stefan P.; Burgard, Gerald; et al.
<x xml:space="preserve">Abstract</x> Background and Objectives The incidence of infectious complications associated with continuous regional anesthesia techniques is a matter of concern. Our objective was to determine whether patients suffering from diabetes are at an increased risk of catheter-related infectious complications. Methods The German Network for Regional Anaesthesia database was analyzed between 2007 and 2012. After proof of plausibility, data of 36, 881 patients undergoing continuous regional anesthesia were grouped in I: no diabetes (n = 32, 891) and II: any diabetes (n = 3990). The analysis focused on catheter-related infections after strict definition. Differences among the groups were tested with t and χ2 tests. Odds ratios were calculated with logistic regression and adjusted for potential confounders. Results Patients with a diagnosis of diabetes had an increased incidence of catheter-related infections (no diabetes 3.0% vs any diabetes 4.2%; P < 0.001). Among all patients, diabetes remained an independent risk factor for infections for all sites after the adjustment for potential confounders (odds ratio [OR] = 1.26; 95% confidence interval [95% CI], 1.02–1.55; P = 0.036). The risk of infection was significantly increased in peripheral catheters only in the lower limb (adjusted OR = 2.42; 95% CI, 1.05–5.57; P = 0.039). If neuraxial catheters were used, the risk was significantly increased only in lumbar epidural (adjusted OR = 2.09; 95% CI, 1.18–3.73; P = 0.012) for diabetic patients compared with nondiabetic patients. Conclusions The presence of diabetes is associated with an increased risk for catheter-related infections in lower limb and lumbar epidural. Specific care should be taken to avoid and detect infections in this population.